COMPARISON OF INTRAOPERATIVE WOUND IRRIGATION WITH AQUEOUS POVIDONE-IODINE SOLUTION TO NORMAL SALINE IN PREVENTING SURGICAL SITE INFECTIONS - Ali, Aabid; Din, Syed Shams; Baig, Inayatullah; Hussain, Mirza Tassawar; Sadiq, Abdullah; Syed, Aqsa (Journal of Ayub Medical College Abbottabad, 2023)
Background: A surgical site infection (SSI) is a wound infection caused by pathogens, particularly bacteria, that occurs within 30 days of the surgery. Various methods have been employed in order to minimize the rates of infection one of which is intra-operative wound irrigation. This study aims to compare the frequency of surgical site infections after wound irrigation of contaminated and dirty wounds with normal saline and aqueous povidone-iodine solutions. Methods: This randomized controlled trial was carried out in the surgical department of Federal Government Polyclinic Hospital from January to December 2022. A total of 180 patients were randomly divided into two equal groups using blocked randomization. Group A had normal saline irrigation while Group B had aqueous povidone-iodine irrigation before surgical incision closure. Patients were followed till 30th post-operative day. Data was collected, entered and analyzed using SPSS 20.0. Results: A total of 180 patients were recruited in this study, equally divided into Group A and Group B with 90 patients each. Fifty-three patients (58.9%) from group-A and 58 patients (64.4%) from group-B were having contaminated wounds and 37 patients (41.1%) and 32 patients (35.6%) had dirty wounds respectively. Surgical site infection was found in 29 patients (32.2%) of group-A and 26 patients (28.8%) of group-B (p=0.627). there was no significant difference between the two groups with respect to surgical site infection. Conclusion: Irrigation of surgical wounds with aqueous povidone-iodine solution before primary closure was statistically similar to normal saline in preventing surgical site infections in contaminated and dirty wounds.